2012
DOI: 10.29079/vol11iss1art177
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study for the prevalence of Neospora caninum in Dairy & Beef cattle in some Iraqi provinces

Abstract: A Seroepidemiological study of Neospora caninum was conducted in Al-Muthana and Al-Nasseria provinces, Iraq on 800 cows serum sample by using commercial Elisa kit. the overall seroprevalence ratio of Neospora caninum was 17.5%, on provincial basis Neospora caninum infection was present in these provinces that was 16 %, 18.4% in Al-Muthana, and Al-Nasseria provinces respectively,which non significant differences between provinces (P<0.05), Comparisons of N.caninum serological status with age groups (5-8 y) show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A study in Iraq on Buffaloes was performed and found about 20 % prevalence of N. caninum (7). The prevalence of N. caninum was 17.5% in dairy and beef cattle in other Iraqi provinces (8). This result was the first investigation of N. caninum among Iraqi cattle in Kirkuk, which indicated that the parasite is present, and at a high level with percentage of 28.6%.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A study in Iraq on Buffaloes was performed and found about 20 % prevalence of N. caninum (7). The prevalence of N. caninum was 17.5% in dairy and beef cattle in other Iraqi provinces (8). This result was the first investigation of N. caninum among Iraqi cattle in Kirkuk, which indicated that the parasite is present, and at a high level with percentage of 28.6%.…”
Section: Discussionmentioning
confidence: 70%
“…Neospora caninum is seen as one of the world's most significant causes of abortion in the cattle. There are reports of infection in other animals including sheep, goat, deer and horse (8). Yearly, economic loss due to neosporosis in Australia in beef and dairy cattle is considered 25 and 85 million respectively.…”
Section: Discussionmentioning
confidence: 99%